2004
DOI: 10.1097/00001756-200403010-00004
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in blood–nerve barrier function and tight-junction protein expression within the rat dorsal root ganglion

Abstract: To elucidate blood-nerve barrier function and tight-junction protein expression in the dorsal root ganglion (DRG), we analyzed the vascular permeability in the rat DRG by i.v. administration of fluorescent Evans-blue albumin (EBA) and compared it with the localization of claudin-1, claudin-5, and occludin by immunoconfocal microscopy. In the cell body-rich area within the DRG, extravascular leakage of EBA was noted and claudin-5 but neither claudin-1 nor occludin was detected. Conversely, in the nerve fiber-ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 17 publications
2
58
0
1
Order By: Relevance
“…6 A) (Kvajo et al, 2004). The high amount of fibrin observed despite a higher level of tPA activity may be explained by the strong inhibition of thrombin by PN-1 (Baker et al, 1980;Monard, 1993;Knauer et al, 2000), which has been shown to increase after sciatic nerve injury (Friedmann et al, 1999;Hirakawa et al, 2003Hirakawa et al, , 2004. This suggests that generation of fibrin overcomes the tPA fibrinolytic effect in mice lacking PN-1.…”
Section: Discussionmentioning
confidence: 99%
“…6 A) (Kvajo et al, 2004). The high amount of fibrin observed despite a higher level of tPA activity may be explained by the strong inhibition of thrombin by PN-1 (Baker et al, 1980;Monard, 1993;Knauer et al, 2000), which has been shown to increase after sciatic nerve injury (Friedmann et al, 1999;Hirakawa et al, 2003Hirakawa et al, , 2004. This suggests that generation of fibrin overcomes the tPA fibrinolytic effect in mice lacking PN-1.…”
Section: Discussionmentioning
confidence: 99%
“…Within the dorsal root ganglia there are no synaptic contacts between neurons however, the somata have microvilli that appear to contribute to the observed interactions between the neuronal somata and between neuronal somata and their surrounding satellite glia cells (Pannese, 2002;Takeda et al, 2009). Moreover, the lack of a nerve-blood barrier also exposes the somata within the dorsal root ganglia to plasma molecules that can modulate their function (Abram et al, 2006;Hirakawa et al, 2004). Each soma is completely surrounded by a layer of satellite glia cells ( Figure 1); and together the soma and satellite glia cells form a single anatomical and functional unit (Hanani, 2005;Pannese, 1981).…”
Section: Dorsal Root Ganglia Morphologymentioning
confidence: 99%
“…Some of the peripheral nerve injury-induced functional changes in the dorsal root ganglia sensory neurons are believed to be important for the initiation and sustained alteration of the activity of the spinal cord neurons and in turn of the brain neurons (central sensitization) that underly chronic neuropathic pain (Harris et al, 1996;Jang et al, 2007;Lee et al, 2003;Liu and Salter, 2010;Obata et al, 2003;Ringkamp and Meyer, 2005). Second, although the dorsal root ganglia is surrounded by a thick connective tissue capsule, the dorsal root ganglia is not protected by a "blood-nerve barrier", as it is the rest of the peripheral nervous system (Abram et al, 2006;Hirakawa et al, 2004). Hence the somata of dorsal root ganglia sensory neurons as well as their surrounding satellite glia cells can be specifically targeted (with respect to the rest of the nervous system including the central nervous system that is also protected by the "blood-brain barrier") with pharmacological agents.…”
Section: Dorsal Root Ganglia As a Pharmacological Target To Avoid Thementioning
confidence: 99%
“…In contrast with peripheral nerves in rats, 24 the capillaries in the DRG are much more permeable to nanoparticles, such as serum albumin (70 kDa, 8 nm 24 in diameter), 25,26 horseradish peroxidase (40 kDa, 2.5-5.0 nm), 27,28 and dextrans of various sizes (3-150 kDa, 3-17 nm). 24 Therefore, following injections of PTX/CRE formulations, PTX rapidly adheres to albumin 29 and circulates in the blood as albumin-bound PTX particles (≈8 nm) 24 that must be small enough to leak from the blood vessels into the DRG.…”
Section: Introductionmentioning
confidence: 99%
“…24 Therefore, following injections of PTX/CRE formulations, PTX rapidly adheres to albumin 29 and circulates in the blood as albumin-bound PTX particles (≈8 nm) 24 that must be small enough to leak from the blood vessels into the DRG. [24][25][26] Subsequent extravasation into DRG parenchyma seems to result in significantly higher and more sustained distributions of PTX in the DRG of PTX/ CRE-treated rodents. 14,16,17,23,30 In contrast, NK105 is ~90 nm in diameter 4 and may be excluded from the DRG, thus limiting the distribution of PTX to the DRG.…”
Section: Introductionmentioning
confidence: 99%